2013
DOI: 10.7705/biomedica.v33i4.805
|View full text |Cite
|
Sign up to set email alerts
|

Caracterización de la expresión de nCD64 en neutrófilos y de los niveles de s-TREM-1 y HMGB-1 en pacientes con sospecha de infección admitidos en el departamento de emergencias

Abstract: Introduction:The nCD64 receptor, the soluble triggering receptor expressed in myeloid cells (s-TREM-1), and the high mobility group-box 1 protein (HMGB-1) have been proposed as significant mediators in sepsis. Objective: To evaluate the prognostic value of these markers in patients with suspected infection recently admitted in an emergency department (ED). Materials and methods:All patients who presented to the ED with suspected infection were eligible for enrollment in this study. Baseline clinical data, Sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…This study suggests that the use of human immunoglobulin in the treatment of pediatric severe pneumonia can regulate the Th1/Th2 balance and avoid excessive activation of Th2. [31][32][33][34][35][36][37]. The results of this study showed that the levels of IL-6, IL-8 and hsCRP in the peripheral blood of both groups were significantly lower than those before treatment, and the levels in the observation group were significantly lower than those in the control group.…”
Section: Discussionmentioning
confidence: 52%
“…This study suggests that the use of human immunoglobulin in the treatment of pediatric severe pneumonia can regulate the Th1/Th2 balance and avoid excessive activation of Th2. [31][32][33][34][35][36][37]. The results of this study showed that the levels of IL-6, IL-8 and hsCRP in the peripheral blood of both groups were significantly lower than those before treatment, and the levels in the observation group were significantly lower than those in the control group.…”
Section: Discussionmentioning
confidence: 52%
“…[14,15] Soluble triggering receptor expressed on myeloid cells 1 (sTREM-1) proteins are detected in patients suffering from severe infectious diseases including pneumonia, sepsis, and chronic bowel disease. [16,17] Elevated level of sTREM-1 is associated with the disease severity and adverse outcome in patients with sepsis and lower respiratory tract infection. [18,19] …”
Section: Introductionmentioning
confidence: 99%